Viral diversity and dynamics in an infant gut - Breitbart, Mya; Haynes, Matthew; Kelley, Scott; Angly, Florent; Edwards, Robert A.; Felts, Ben; Mahaffy, Joseph M.; Mueller, Jennifer; Nulton, James; Rayhawk, Steve; Rodriguez-Brito, Beltran; Salamon, Peter; et al. (Research in microbiology, 2008)
Metagenomic sequencing of DNA viruses from the feces of a healthy week-old infant revealed a viral community with extremely low diversity. The identifiable sequences were dominated by phages, which likely influence the diversity and abundance of co-occurring microbes. The most abundant fecal viral sequences did not originate from breast milk or formula, suggesting a non-dietary initial source of viruses. Certain sequences were stable in the infant's gut over the first 3 months of life, but microarray experiments demonstrated that the overall viral community composition changed dramatically between 1 and 2 weeks of age.